2021
DOI: 10.1016/j.patter.2020.100176
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering social-contextual and individual mental health factors associated with violence via computational inference

Abstract: Summary The identification of human violence determinants has sparked multiple questions from different academic fields. Innovative methodological assessments of the weight and interaction of multiple determinants are still required. Here, we examine multiple features potentially associated with confessed acts of violence in ex-members of illegal armed groups in Colombia (N = 26,349) through deep learning and feature-derived machine learning. We assessed 162 social-contextual and individual mental h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 136 publications
(303 reference statements)
0
7
0
Order By: Relevance
“…First, we conducted the best search for the most appropriate set of hyperparameters using cross-validation to obtain the best possible generalization results 60 , 61 . For each model, we implemented a Bayesian optimization approach for hyperparameter tuning, with cross-validation = 3 and ten iterations, on 75% of the data (training dataset), and evaluated the results on a validation dataset (25% of the data).…”
Section: Methodsmentioning
confidence: 99%
“…First, we conducted the best search for the most appropriate set of hyperparameters using cross-validation to obtain the best possible generalization results 60 , 61 . For each model, we implemented a Bayesian optimization approach for hyperparameter tuning, with cross-validation = 3 and ten iterations, on 75% of the data (training dataset), and evaluated the results on a validation dataset (25% of the data).…”
Section: Methodsmentioning
confidence: 99%
“…The main limitation of this study resides in the lack of steps to control the effects of demographic covariates (age, sex, and ages of formal education) 8,53 on dementia classification (but see the confirmation results using matched samples in Appendix C). Future pipeline implementations will allow for the inclusion of demographics in the classification, as is done elsewhere 16,35,36 . Likewise, future studies must address statistical approaches to validate the best pipelines created by the synergy of available choices (options for spatial normalization, EEG source reconstruction, connectivity metrics, and classification algorithms).…”
Section: Discussionmentioning
confidence: 99%
“…Studies with large samples of normative people using self-reports have repeatedly demonstrated strong associations between radical/extremist views and dogmatic intolerance both on political and religious issues Krouwel, 2017, 2019). The predictive capacity of measures based on individual traits for extremist political adscription is now increasingly grounded (Finkel et al, 2020;Hibbing, 2021;Santamaria-Garcia et al, 2021;Zmigrod et al, 2021).…”
Section: Discussionmentioning
confidence: 99%